The classification of economic activity - Travis J. Berge; Oscar Jordà (University of California, Department of Economics, 2009)
The Business Cycle Dating Committee (BCDC) of the National Bureau of Economic Research provides a historical chronology of business cycle turning points. This paper investigates three central aspects about this chronology: (1) How skillful is the BCDC in classifying economic activity into expansions and recessions? (2) Which indices of business conditions best capture the current but unobservable state of the business cycle? And (3) Which indicators predict future turning points best and at what horizons? We answer each of these questions in detail with methods novel to economics designed to assess classification ability. In the process we clarify several important features of business cycle phenomena.
Keywords: E32; E37; C14; 330; business cycle turning points; Receiver Operating Characteristics (ROC) curve; Business Cycle Dating Committee of the National Bureau of Economic Research